Precision surveying : the principles and geomatics practice - Ogundare, John Olusegun (Hoboken : John Wiley and Sons, Inc., 2016)
'A comprehensive overview of high precision surveying, including recent developments in geomatics and their applications'--
Includes bibliographical references and index.
Keywords: Surveying; TECHNOLOGY & ENGINEERING / Civil / General